Pengaruh Edukasi Gizi terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Trimester II - Bayu Larasati Wulandari; Fitri Andriani; Dwi Feni Pebriani Br Tarigan; Nurmala Sari; Sastrika Handayani Marpaung (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Anemia in pregnant women remains a public health problem that impacts the health of both the mother and the fetus. One effort to prevent anemia is through nutrition education, which aims to increase pregnant women's knowledge about consuming foods rich in iron and other essential nutrients. This study aimed to analyze the effect of nutrition education on increasing hemoglobin levels in pregnant women in the second trimester. The study used a quasi-experimental design with a pretest–posttest approach. The study sample consisted of 30 pregnant women in the second trimester selected using a purposive sampling technique. Hemoglobin levels were measured using a hemoglobinometer before and after four weeks of nutrition education. Data analysis used a paired t-test. The results showed an average increase in hemoglobin levels from 10.5 ± 0.8 g/dL to 11.7 ± 0.9 g/dL (p < 0.001). It was concluded that nutrition education significantly increased hemoglobin levels in pregnant women in the second trimester.